Efficacy of primary preservice teachers for gender equality: the state of knowledge and practice and attitudes for gender in Morocco - Kmiti, Said; Azeroual, Sidi Hassane (Frontiers in Education, 2025)
PurposeThis article describes the current state of self-efficacy among preservice teachers’ in mainstreaming gender equality in primary education using the TEGEP scale.Design/methodology/approachA survey was administered with a group of preservice teachers at the Regional Center for Education and Training Professions in Beni Mellal-Khenifra/Khenifra annex, Morocco. Using a convenience sample of primary education teachers, 111 participants were asked to assess their efficacy in knowledge and awareness, teaching methods, and attitudes related to gender equality using a six-point Likert scale.FindingsThe preservice teachers reported positive perceptions in adopting gender-responsive teaching methods and in attitudes that basically consolidate gender equality. However, the results also highlight their lack of necessary knowledge to translate these positive attitudes and good practices into sustainable gender equality practices. The level of self-efficacy was found to be moderate in gender knowledge and awareness, but strong in practices and attitudes.Originality/valueThis study provides particularly useful preliminary results in describing the current state of training in mainstreaming gender in teacher training programs. It serves as a starting point for further studies to advance research on gender equality in educational settings. Given the absence of a sustainable approach to gender equality education, integrating gender equality into training is beneficial in instilling good practices and positive attitudes in preservice teachers’ practices, contributing to the promotion of gender equality values.